Hybrid Procedure for Acute Stanford Type A Aortic Dissection with Aberrant Right Subclavian Artery. Issue 3 (16th June 2014) - Ren, Changwei; Sun, Lizhong; Huang, Lianjun; Lai, Yongqiang; Yang, Sheng; Xu, Shangdong
Abstract Aberrant right subclavian artery (ARSA) is an uncommon congenital vascular abnormality. Acute Stanford type A aortic dissection with ARSA is rare. We report a strategy for Stanford type A aortic dissection with ARSA. The ascending aorta and the total aortic arch were replaced and a frozen elephant trunk was implanted into the descending aorta. The right subclavian artery was reconstructed with the perfusion branch of a four‐branch prosthetic graft. Two weeks later, the proximal part of the ARSA was sealed with a vascular plug. doi: 10.1111/jocs.12386 (J Card Surg 2015;30:274–275)